Orange world and other stories [large type] - Russell, Karen, 1981- (Random House Large Print, 2019)
"From the Pulitzer finalist and universally beloved author of the New York Times best sellers Swamplandia! and Vampires in the Lemon Grove, a stunning new collection of short fiction that showcases Karen Russell's extraordinary gifts of language and imagination"--